The L3-6 chondritic regolith breccia Northwest Africa (NWA) 869: (I) Petrology, chemistry, oxygen isotopes, and Ar-Ar age determinations - Metzler, Knut; Hopp, Jens; Trieloff, Mario (Meteoritics & planetary science, 2011)
Northwest Africa (NWA) 869 consists of thousands of individual stones with an estimated total weight of about 7 metric tons. It is an L3-6 chondrite and probably represents the largest sample of the rare regolith breccias from the L-chondrite asteroid. It contains unequilibrated and equilibrated chondrite clasts, some of which display shock-darkening. Impact melt rocks (IMRs), both clast-free and clast-poor, are strongly depleted in Fe,Ni metal, and sulfides. An unequilibrated microbreccia, two different light inclusions and two different SiO2-bearing objects were found. Although the matrix of this breccia appears partly clastic, it is not a simple mixture of fine-grained debris formed from the above lithologies, but mainly represents an additional specific lithology of low petrologic type. We speculate that this material stems from a region of the parent body that was only weakly consolidated. One IMR clast and one SiO2-bearing object show Δ17O values similar to bulk NWA 869, suggesting that both are related to the host rock. In contrast, one light inclusion and one IMR clast appear to be unrelated to NWA 869, suggesting that the IMR clast is contaminated with impactor material. 40Ar-39Ar analyses of a type 4 chondrite clast yield a plateau age of 4402 ± 7 Ma, which is interpreted to be the result of impact heating. Other impact events are recorded by an IMR clast at 1790 ± 36 Ma and a shock-darkened clast at 2216 ± 40 Ma, demonstrating that NWA 869 escaped major reset in the course of the event at approximately 470 Ma that affected many L-chondrites.
Gesehen am 28.01.2015